Slovensko tekstilstvo skozi čas (obdobje od 1930. do začetka 80-ih let) - Debevc, Jože (2023)
Slovenian Textile Industry Over Time (the Period from the 1930s to the Beginning of the 80s). In front of you are memories and glimpses, an attempt at a historical record of Slovenian textiles and the people - textile workers, who left their mark on the development of Slovenian textiles in the period from 1930 to the beginning of the 80s.
Keywords: Slovenian textile industry; history; University of Maribor; study; Faculty of Mechanical Engineering